The dynamics of poverty targeting - Hillebrecht, Michael; Klonner, Stefan; Pacere, Noraogo A. (Journal of development economics, 2023)
Several recent papers have compared the ability of proxy-means testing (PMT) and community-based targeting (CBT) to identify consumption-poor households. Motivated by the facts that targeted benefits typically reach beneficiaries with a substantial time lag and that transitions into and out of poverty are frequent, we assess PMT’s and CBT’s performance during the years following the targeting exercise. With original data from Burkina Faso, we replicate the finding that PMT outperforms CBT at baseline. But this pattern disappears for households’ poverty status 12 and 30 months later where both methods perform equally well. For real-world welfare programs where benefits typically accrue with a substantial time lag, our results suggest that CBT’s targeting performance is better than commonly thought.